Because of Winn-Dixie - Wang, Wayne, 1949-; Daniels, Jeff, 1955-; Tyson, Cicely; Matthews, Dave, 1967-; Saint, Eva Marie, 1924-; Robb, AnnaSophia, 1993-; Lindenlaub, Karl Walter; Portman, Rachel; DiCamillo, Kate.; Twentieth Century Fox Home Entertainment, Inc. ([Beverly Hills, Calif.] : 20th Century Fox Home Entertainment, 2005)
A young girl's life is changed by a scruffy, fun-loving pooch she names Winn-Dixie. The special bond between them works magic on her reserved dad and the eccentric townspeople they meet during one unforgettable summer.
DVD, region 1, full screen (1.33:1) or widescreen (1.85:1) presentations; Dolby Digital 5.1, Dolby surround.
English, Spanish or French soundtracks with English or Spanish subtitles. Closed-captioned.
Jeff Daniels, Cicely Tyson, Dave Matthews, Eva Marie Saint, AnnaSophia Robb, Elle Fanning, Courtney Jines, Nick Price, Luke Benward, Marca Price.
Director of photography, Karl Walter Lindenlaub ; editor, Deirdre Slevin ; music, Rachel Portman ; costume designer, Hope Hanafin ; production designer, Donald Graham Burt.
Based on the novel by Kate DiCamillo.
"Exclusive Target limited edition"--Container.
Keywords: Dogs -- Juvenile drama; City and town life -- Juvenile drama; Friendship -- Juvenile drama; Dogs -- Drama; Friendship -- Drama; Feature films; Children's films; Video recordings for hard of hearing people